On Projective 3-Space Over Galois Field - A. SH. Al-Mukhtar (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The purpose of this paper is to give the definition of projective 3-space PG(3,q) over Galois field GF(q), q = pm for some prime number p and some integer m.